2007
DOI: 10.1002/art.22764
|View full text |Cite
|
Sign up to set email alerts
|

Do proton‐pump inhibitors confer additional gastrointestinal protection in patients given celecoxib?

Abstract: Objective. Celecoxib has a superior upper-gastrointestinal (GI) safety profile compared with nonselective nonsteroidal antiinflammatory drugs (NS-NSAIDs). It is unclear whether the utilization of a proton-pump inhibitor (PPI) with celecoxib confers additional protection in elderly patients. We assessed the association between GI hospitalizations and use of celecoxib with a PPI versus celecoxib alone, and NS-NSAIDs with a PPI or NS-NSAIDs alone in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 25 publications
1
21
1
3
Order By: Relevance
“…It is presumed but not proven that the combination of a PPI plus coxib may be safest from a GI standpoint. • An observational study suggests an additional 25% risk reduction in patients who use PPI plus celecoxib when compared with patients taking celecoxib alone [44]. • This combination is cost effective [31], providing an additional 50% reduction in the incidence of upper GI complications compared with competing strategies such as coxib alone or NSAID plus PPI.…”
Section: Combination Of Both Strategies: Coxibs Plus Ppimentioning
confidence: 98%
“…It is presumed but not proven that the combination of a PPI plus coxib may be safest from a GI standpoint. • An observational study suggests an additional 25% risk reduction in patients who use PPI plus celecoxib when compared with patients taking celecoxib alone [44]. • This combination is cost effective [31], providing an additional 50% reduction in the incidence of upper GI complications compared with competing strategies such as coxib alone or NSAID plus PPI.…”
Section: Combination Of Both Strategies: Coxibs Plus Ppimentioning
confidence: 98%
“…13 This observation was confirmed in an observational case-control study, using a population-based claims-database in Canada, in which both gastroprotective strategies were similarly effective in the prevention of NSAID-related UGI events, but it did not address the lack of adherence to PPIs. 14 However, we and others have demonstrated that in real life, GPA adherence during nsNSAID use is an important factor to consider when evaluating and comparing the effectiveness of different gastroprotective strategies.…”
Section: Introductionmentioning
confidence: 91%
“…Based on gastrointestinal endoscopy data [21], COX-2-selective agents likely are safer options at all levels of risk compared with nonselective NSAIDs; however, due to issues of cost compared with generic nonselective NSAIDs, their use has been promoted primarily in patients at higher gastrointestinal risk (eg, two or more identified gastrointestinal risk factors). Recent data also have confirmed that a further reduction in gastrointestinal bleeding risk can be achieved in high-risk patients older than 70 years of age who require anti-inflammatory drugs by adding a PPI to a COX-2-selective inhibitor [22].…”
Section: Introductionmentioning
confidence: 94%